1999
DOI: 10.1136/bmj.318.7181.421
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and perinatal risk factors for schizophrenia, affective psychosis, and reactive psychosis of early onset: case-control study   Prenatal and perinatal risk factors for early onset schizophrenia, affective psychosis, and reactive psychosis

Abstract: Objective To examine prenatal and perinatal risk factors for subsequent development of schizophrenia and affective and reactive psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(165 citation statements)
references
References 36 publications
10
152
1
2
Order By: Relevance
“…An association between small head circumference at birth and the later development of schizophrenia was confirmed in a number of previous studies (Cantor-Graae et al, 1998;Hultman et al, 1999;Ichiki et al, 2000;Kunugi et al, 1996;McNeil et al, 2000). In accordance with our results, three of these studies showed a reduction in the risk related to small head circumference, after controlling for gestational age (Cantor-Graae et al, 1998;Kunugi et al, 1996;McNeil et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…An association between small head circumference at birth and the later development of schizophrenia was confirmed in a number of previous studies (Cantor-Graae et al, 1998;Hultman et al, 1999;Ichiki et al, 2000;Kunugi et al, 1996;McNeil et al, 2000). In accordance with our results, three of these studies showed a reduction in the risk related to small head circumference, after controlling for gestational age (Cantor-Graae et al, 1998;Kunugi et al, 1996;McNeil et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, a large number of epidemiological studies have demonstrated that perinatal complications, often involving fetal or neonatal hypoxia, are associated with increased risk for the development of schizophrenia (e.g., Geddes and Lawrie 1995;Jones et al 1998;Dalman et al 1999;Hultman et al 1999;Zornberg et al 2000; see review by McNeil 1995).…”
Section: Schizophrenia Is Associated With Increased Birth Complicatiomentioning
confidence: 99%
“…Obstetric and neonatal complications may have a long-term influence on offspring mental health, including risks of schizophrenia [7], depression [8], and suicidal acts [9][10][11][12]. Maternal smoking has been recognized as one of the most important risk factors for adverse pregnancy outcomes, including placental complications, fetal growth restriction, preterm birth and associated conditions [13].…”
Section: Introductionmentioning
confidence: 99%